Development of common work breakdown structure (WBS) for school project - Abdullah, Azhar (2006)
A lot have been said about delayed school projects. Among the main factors that contribute to the problem are lacking of experience among the contractor, adopting non suitable and non detailed scheduling method for project monitoring. Ministry of Works and The Ministry of Education are two main bodies that offer school tender. They used two different methods of tendering procedure which come out with two different methods of project scheduling and monitoring. Bear in mind that every scheduling technique has its own limitation. Proper preparation of scheduling however will help in avoiding delay of completion. This project explore the potential of Work Breakdown Structure (WBS) as a tool to enhance the current scheduling method. Focus is given only on school projects. Among the objectives of this project are to identified the normal steps in preparing WBS in the project scheduling and to develop a common Work Breakdown Structure specifically for school projects. The methodology adopted involving literature search, interview with authorities, consultants and contractors who have experienced in school projects. Analysis based on the structured interview was used to identify the main reason for project delay. Result from the survey has shown that reasons for school delayed are no proper scheduling tools and lack of experience and bad site management. A newly developed common WBS for school project is also proposed and used by contractors in assisting them during the preparation of work scheduling on site.